Cone beam computed tomography: A boon for maxillofacial imaging - Sreenivas Rao Ghali; Girish Katti; Syed Shahbaz; Chandrika Katti (Wolters Kluwer Medknow Publications, 2017)
In day to day practice, the radiographic techniques used individually or in combination suffer from some inherent limits of all planar two-dimensional (2D) projections such as magnification, distortion, superimposition, and misrepresentation of anatomic structures. The introduction of cone-beam computed tomography (CBCT), specifically dedicated to imaging the maxillofacial region, heralds a major shift from 2D to three-dimensional (3D) approach. It provides a complete 3D view of the maxilla, mandible, teeth, and supporting structures with relatively high resolution allowing a more accurate diagnosis, treatment planning and monitoring, and analysis of outcomes than conventional 2D images, along with low radiation exposure to the patient. CBCT has opened up new vistas for the use of 3D imaging as a diagnostic and treatment planning tool in dentistry. This paper provides an overview of the imaging principles, underlying technology, dental applications, and in particular focuses on the emerging role of CBCT in dentistry.